Upaya Pencegahan Karies: Penyuluhan Kesehatan Gigi dan Mulut serta Pemberian Topikal Aplikasi Fluoride pada Anak Berkebutuhan Khusus di Kota Makassar - Syakriani Syahrir; Harun Achmad; Wiwik Elnangti Wijaya; Yayah Inayah (Universitas Hasanuddin, 2020)
Efforts to maintain dental and oral health in children with special needs require special attention because individuals with special needs are a group that has a high caries risk. This is due to the physical and mental limitations experienced by children with special needs so that it can affect the level of education and the ability of children to maintain healthy teeth and mouth. This outreach activity was carried out using the method of showing educational videos and live demonstrations with props. The results of counseling on how to brush their teeth properly were then demonstrated by all participants in the joint toothbrush activity. Application of topical fluoride to children with special needs is also carried out in this activity as an effort to prevent caries.